2007
DOI: 10.1007/s10209-007-0074-z
|View full text |Cite
|
Sign up to set email alerts
|

Mobile computer Web-application design in medicine: some research based guidelines

Abstract: Designing Web-applications is considerably different for mobile computers (handhelds, Personal Digital Assistants) than for desktop computers. The screen size and system resources are more limited and end-users interact differently. Consequently, detecting handheld-browsers on the server side and delivering pages optimized for a small client form factor is inevitable. The authors discuss their experiences during the design and development of an application for medical research, which was designed for both mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 50 publications
(49 reference statements)
1
44
0
Order By: Relevance
“…Heuristic evaluation was completed for both the old and the new GUIs, following some guidelines from the medical domain -which is a similar safety-critical application area [13], [14], [15], [16].…”
Section: Methodsmentioning
confidence: 99%
“…Heuristic evaluation was completed for both the old and the new GUIs, following some guidelines from the medical domain -which is a similar safety-critical application area [13], [14], [15], [16].…”
Section: Methodsmentioning
confidence: 99%
“…The acceptance of mobile devices depends above all on their usefulness and their usability [14]. When using such devices it is quite apparent that the limited space on their screens involves significant challenges to the developers and usability engineers [15], [16], [17]. For example, one study demonstrated that a touch-based mobile device can be used successfully within the healthcare context only if it has an appropriate design [18].…”
Section: Mobile Devicesmentioning
confidence: 99%
“…Consequently, the data acquisition should have as little disruptive effect on the workflow of the medical professionals as possible. In the past, solutions for data input on mobile applications have been tested in the field [7,15,17,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…A key issue of any such information system is the acquisition of textual information. However, extensive text entry on mobile devices is principally to be avoided and a simple and easy to use interface, in accordance with the maxim less is more, is a supreme necessity [22].…”
Section: Introductionmentioning
confidence: 99%